Improving students’ ability of first grade students in operationalizing sum and reduction in mathematics subjects by using the assistance of congkrit items in sd negeri no. 16 sungai apit kecamatan apit kabupaten siak - Darmawati Darmawati (Fakultas Sastra Universitas Ekasakti, 2018)
Education is the responsibility of the school family and the environment. The success of the three component education is crucial. In addition to these three components, learning methods or strategies, learning tools are also absolutely necessary. The problem of this research is how to use concrete objects can increase the ability of students of Class I in SD Negeri No. 16 Sungai Apit Kecamatan Sungai Siak Kabupaten Siak in operationalizing addition and subtraction in mathematics. This study aims to improve students' ability in operationalizing the addition and subtraction with the help of concrete objects, also expected to benefit students, researchers, and parents. To achieve the purpose of the research, the researcher used classroom action research against the first grade students of SD Negeri 16 Apit Sungai Siak Kecamatan Sungai Apit Kabupaten Siak as many as 37 students who performed in 2 cycles. The method used in this study is a qualitative approach that describes the actual problems that exist in the field and then reflected and analyzed based on the theory that support followed by the implementation of research in the field.Data obtained in this study through observation discussion and evaluation. The results of this study indicate an increase of priminaliry activities, cycle I and cycle II.In priminaliry study, students who experience mastery learning as much as 35% after the action with the tools of concrete objects.Student learning completeness in the first cycle rose to 97% followed by the next cycle all students experience complete mastery learning. The conclusion that can be taken is that concrete objects can help students in operationalizing the addition and reduction of numbers on learning Class I Mathematics, so that learning achievement progress. Other findings children become happy, confident in doing the learning process. Thus it can be suggested that the implementation of education should be environmentally friendly because the environment provides a lot of tools that are cheap, easy to obtain and easily recognized by children.